Bone Metastases of Glioblastoma: A Case Report and Review of the Literature - Zhang, Wei; Cai, Yuan-yuan; Wang, Xiao-li; Wang, Xiao-xiao; Li, Yang; Han, Gui-yan; Chu, Yu-jing; Zhang, Yun-xiang; Hao, Fu-rong (Frontiers in Oncology, 2021)
Background: Glioblastoma (GBM) is the most common primary intracranial tumor and originates from the small pool of adult neural stem and progenitor cells (NSPCs). According to the World Health Organization (WHO) classification of brain tumors, gliomas are classified into grades I-IV, and GBM is defined as the highest grade (IV). GBM can be disseminated by cerebrospinal fluid (CSF), but extracranial metastasis is rare. Additionally, the pathway and mechanism involved remain unclear. Case Presentation: We report a rare case of left temporal lobe GBM with multiple bone metastases and soft tissue metastasis. This 49-year-old right-handed man who was diagnosed with GBM underwent surgery on May 9, 2017, followed by radiochemotherapy in June 2017. On August 13, 2019, local relapse was found. Then, the patient received a second surgery but not radiochemotherapy. In November 2019, the patient reported suffering from low back pain for nearly one month. On December 6, 2019, magnetic resonance imaging (MRI) of the thoracolumbar vertebrae and abdominal computed tomography (CT) confirmed metastases on the 9th posterior rib on the right, the third anterior rib on the left, and the T7 and T10 vertebrae and their appendages. CT-guided rib space-occupying puncture biopsy was performed, and GBM was identified by pathology. Conclusion: We should pay attention to extracranial metastasis of GBM. Timely detection and early treatment improve overall quality of patients’ life. The extracranial metastasis in this patient may have occurred through the spinal nerve root or intercostal nerve. Further clinical observations are required to clarify the pathway and mechanism involved.